2015
DOI: 10.1016/j.jas.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Copper processing in the oases of northwest Arabia: technology, alloys and provenance

Abstract: a b s t r a c tVery little is known about early metallurgical activity in the north-western part of the Arabian Peninsula, despite the region's cultural importance. To begin to address this research lacuna, metallurgical remains including crucible fragments, metal dross and a copper artefact were sampled from two oases in northwest Arabia, Qurayyah and Tayma. The metallurgical activity in Qurayyah is dated to the Late Bronze Age, and in Tayma to the Roman/Late Roman period. At both sites we identified evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 34 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…LI data for Sardinian and Cretan ores and objects (Oxalid), as well as Arabian Shield Massive Sulphide Deposits (Bokhari and Kramers, 1982), galena (Stacey et al, 1980) and whole rock data (Ellam et al, 1990), and metal artefacts from Yemen (Weeks et al, 2009) were compared (not shown here), but did not reveal close resemblance to the Pi-Ramesse samples. While it is possible that ore deposits in the Arabian Shield area (Saudi Arabia, Yemen) provided important copper supplies to the LBA eastern Mediterranean (Liu et al, 2015), this hypothesis cannot be further explored in absence of copper ore data.…”
Section: Largest Group -'Egyptian Metal'?mentioning
confidence: 99%
See 2 more Smart Citations
“…LI data for Sardinian and Cretan ores and objects (Oxalid), as well as Arabian Shield Massive Sulphide Deposits (Bokhari and Kramers, 1982), galena (Stacey et al, 1980) and whole rock data (Ellam et al, 1990), and metal artefacts from Yemen (Weeks et al, 2009) were compared (not shown here), but did not reveal close resemblance to the Pi-Ramesse samples. While it is possible that ore deposits in the Arabian Shield area (Saudi Arabia, Yemen) provided important copper supplies to the LBA eastern Mediterranean (Liu et al, 2015), this hypothesis cannot be further explored in absence of copper ore data.…”
Section: Largest Group -'Egyptian Metal'?mentioning
confidence: 99%
“…The well-known Egyptian interactions along the Red Sea with the 'Land of Punt' (Dixon, 2004;Fattovich, 2012;Meeks, 2003) et al, 2009). Though no isotopic evidence is currently available to suggest this, this source is worth considering in the future (Liu et al, 2015).…”
Section: Ramessementioning
confidence: 99%
See 1 more Smart Citation
“…, ) and Cu imported from the oases of north‐west Arabia or from Cyprus (Liu et al . , passim ; Millard ). In addition, alum was imported from Egypt, Sn also from Iranian and Armenian mines (Begemann et al .…”
Section: Discussionmentioning
confidence: 99%
“…This helps to backdate the possible use of the dwarf palm as a religious symbol/cult object.Recent finds in the north-western Arabian oases of Qurraya and Tabukm, may antedate direct contacts between the Southern Levant and the Arabian Peninsula to the Early Bronze Age.Connections between Tayma and the Levant are demonstrated for the final stage of the period (Early Bronze Age IVB) and in the following Middle Bronze Age, and accentuated during the Late Bronze Age (LBA), when political and commercial contacts extended to Egypt, the Mediterranean, Assyria and Babylonia(Liu et al 2015). The establishment of actual trade routes between the southern Arabian Peninsula and the Levant is dated to the LBA, involving the trade of incense and copper(Liu et al 2015), enriched during the Early Iron Age with the trade of iron(Renzi et al 2016). Although the cited studies refer to more recent archaeological periods, it is evident that this geographical area represented a fundamental junction point between…”
mentioning
confidence: 99%